Spletne strani šolske knjižnice OŠ Ivana Cankarja Vrhnika - Nagode Burger, Andreja (Šolska knjižnica, 2012)
In the school year 2011/12 the school library at Primary school Ivan Cankar Vrhnika finally undertook the effort of renovation of its web site. The desire was to give it a fresh look, simplify the design and adding of contents, news and other files. All this is possible with a new service by Arnes, called Blog.arnes.si. The old and new content was easily transferred to this blog. The new look of the web site (knjiznica.blog.arnes.si) has become fully operative. The news and notices are published as they appear, various files can be attached and enhanced with intersting links. The possibility of adding user comments even more enriches the contents. The Arnes service which we used enabled us a very simple preparation of the school library web presentation as well as easy publishing and editing of static content and of various contribution.
Keywords: Arnes; blogi; IKT; informacijska-komunikacijska tehnologija; osnovne šole; spletne strani; šolske knjižnice